(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the main points in the development of key competencies of foreign language learners using the problem-based teaching method. The goal of problem-based learning is to assimilate not only the results of scientific knowledge, but also the formation and development of the student’s intellectual, motivational, and emotional spheres, with an emphasis on the student’s overall development.